ISOLATION AND IDENTIFICATION OF INDIGENOUS BACTERIA USING PCR AND EVALUATION OF THEIR EFFICIENCY IN DEGRADING PYROXSULAM PESTICIDE IN LIQUID CULTURE MEDIA: ISOLATION AND IDENTIFICATION OF INDIGENOUS BACTERIA USING PCR AND EVALUATION OF THEIR EFFICIENCY IN DEGRADING PYROXSULAM PESTICIDE IN LIQUID CULTURE MEDIA (Iraqi Journal of Market Research and Consumer Protection, 2026)
This study aimed to isolate and identify indigenous bacterial strains from soils contaminated with the herbicide pyroxsulam and to assess their ability to degrade the compound in liquid culture media. Soil samples were collected from wheat fields previously treated with the herbicide. Several bacterial isolates were obtained and subjected to morphological characterization and biochemical tests. Identification was further confirmed using polymerase chain reaction (PCR) analysis. The most effective isolate was identified as Paenibacillus alvei based on the results. The degradation capacity of the isolate was determined at three concentrations (36, 52.6 and 112 mg L⁻¹) of the herbicide in nutrient broth. Growth of bacteria was observed for different incubations. The isolate grew in all herbicide concentrations. These demonstrates unequivocal the potential of the isolate to degrade pyroxsulam and thus its applicable potential in the bioremediation of polluted soil.